Porous polybenzimidazole enhanced polyphenylene sulfide composite diaphragm for hydrogen production by alkaline electrolyzed water and preparation method of porous polybenzimidazole enhanced polyphenylene sulfide composite diaphragm
By coating the porous polybenzimidazole enhanced composite membrane on the polyphenylene sulfide membrane, the problems of poor bonding force and insufficient mechanical properties of the composite layer and the base layer are solved, and high hydrophilicity, low ohmic resistance and good mechanical properties are achieved. The composite diaphragm improves the efficiency of hydrogen production by electrolyzing water and the stability of the diaphragm.
Patent Information
- Application Number
- CN202411587107.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
In the existing alkaline electrolytic hydrogen production technology, the composite layer has poor bonding force between the base layer and the composite separator, and the mechanical properties and alkali resistance of the composite separator are insufficient, resulting in low electrolytic efficiency and poor mechanical stability.
Using porous polybenzimidazole enhanced polyphenylene sulfide composite membrane, the cast film liquid is coated on the polyphenylene sulfide membrane, including organic polymer materials based on the polybenzimidazole framework, pore-forming agent PVP and plasticizer PEG, vacuum drying and alkaline soaking, forms a composite separator with high hydrophilicity, low ohmic resistance and good mechanical properties.
The good mechanical properties and bonding force of the composite diaphragm are achieved, the hydrophilicity and conductivity are improved, the surface resistance is reduced, the alkali resistance and stability of the diaphragm are enhanced, and the efficiency of hydrogen production by electrolyzing water is improved.
Smart Images

Figure CN119463287A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen production by water electrolysis, and in particular relates to a porous polybenzimidazole-reinforced polyphenylene sulfide composite diaphragm for hydrogen production by alkaline water electrolysis and a preparation method thereof. Background Art
[0002] Among various water electrolysis technologies, the traditional alkaline water electrolysis (AWE) technology with alkaline electrolyte and porous diaphragm is the most mature and has reached the commercial level. The diaphragm is the core component of water electrolysis, because it not only prevents the hydrogen and oxygen on both sides of the diaphragm from mixing and ensures the purity of the gas, but also needs to reduce the resistance when the conductive ions pass through, and also has certain requirements for mechanical strength.
[0003] Traditional AWE technology uses asbestos with a large pore size (>7μm) as the diaphragm material, but when the temperature is higher than 80℃, there will be stability problems when asbestos comes into contact with the electrolyte. At present, the most commonly used diaphragm in alkaline electrolyzers is polyphenylene sulfide (PPS), which is a diaphragm cloth made of PPS fibers through weaving, spunlace and other processes. PPS is a high-performance special engineering plastic that can maintain stable performance under alkaline and high temperature conditions, so it can be used to prepare alkaline hydrogen production diaphragms. However, the hydrophilicity of polyphenylene sulfide diaphragms is too weak. Poor hydrophilicity will cause the diaphragm cloth to not be fully wetted by the electrolyte, and the ion permeability of the diaphragm will deteriorate. Furthermore, the diaphragm resistance is large, which ultimately makes the electrolysis efficiency of the electrolyzer low, greatly wasting electric energy. In order to improve its hydrophilicity, a hydrophilic coating can be coated on the surface of the diaphragm to form a composite diaphragm with a sandwich structure. The traditional Zirfon diaphragm improves the hydrophilicity of the diaphragm by coating a mixed slurry of polysulfone and zirconium dioxide on the surface of polyphenylene sulfide. Since polysulfone is hydrophobic, in order to improve the conductivity of the diaphragm, a large amount of hydrophilic inorganic particles are usually added to improve the hydrophilicity and conductivity, but its mechanical properties will be greatly reduced. In addition, polysulfone has poor alkali resistance. The Zirfon diaphragm cannot withstand high temperature and concentrated alkali erosion, which can easily cause the coating to crack or fall off.
[0004] Polybenzimidazole (PBI) refers to a class of heterocyclic polymers containing imidazole rings in the repeating unit. It has excellent thermal stability, mechanical stability and chemical stability and is widely used in fire protection, microelectronics, aerospace, oil extraction and automobile fields. When applied to specific ion membrane fields, the imidazole ring structure of PBI gives it special amphoteric properties. It can be doped with proton acid to obtain a cation conductive membrane used in an acidic environment, and can also be doped with alkali to obtain an anion conductive membrane used in an alkaline environment. In addition, the PBI structure can be regulated by changing the type of monomer, which is suitable for large-scale development and is expected to become a new generation of battery ion conductive membrane materials and alkaline hydrogen production diaphragms.
[0005] At present, most polybenzimidazole diaphragms add hydrophilic inorganic particles during the film formation process to improve the hydrophilicity of the diaphragm:
[0006] Patent CN115895014A discloses a method for preparing a highly hydrophilic inorganic doped composite porous polymer anion membrane, which improves the hydrophilicity of the membrane and increases the conductivity by adding a small amount of nano zirconium oxide. However, nano zirconium oxide itself cannot conduct ions, and it has poor compatibility with the PBI matrix and is prone to agglomeration. The low doping amount of the filler limits the improvement of the mechanical properties and ion conductivity of the composite membrane.
[0007] Patent CN115548362A discloses a nano cationic composite membrane for flow batteries and its preparation method, wherein the hydrophilicity of silica microspheres is modified by polyethyleneimine (PEI) and phytic acid (PA), and the prepared hydrophilic mesoporous silica microsphere nanoparticles are dispersed in a polybenzimidazole solution and coated to form a membrane. The addition of inorganic nanoparticles improves the hydrophilicity and ion selectivity of the composite membrane, but the method is complicated to operate, and long-term use will cause the nanoparticles to fall off.
[0008] Patent CN118515905A discloses a method for preparing a polybenzimidazole asymmetric porous membrane and its application as an alkaline water electrolysis membrane, wherein an NPBI solution containing a pore-forming agent additive is cast in a DMSO solvent, and then a selective solvent is used to replace the pore-forming agent and convert it into a porous membrane. The porous structure of the NPBI porous membrane provides a channel for ion transmission, increases the absorption of electrolytes, and effectively reduces the surface resistance, but at the same time, the porous structure also reduces the strength of the membrane, and long-term use can easily cause the membrane to rupture.
[0009] Yuke Su et al. (Su, Y. et al. Building water molecule chains in polybenzimidazole membrane toward superior vanadium redox flowbattery. Chemical Engineering Journal 485, doi: 10.1016 / j.cej.2024.149838 (2024).) used KOH / ethanol as casting solvent, cut off the hydrogen bonds between PBI chains through a deprotonation strategy, weakened the interaction between PBI chains, expanded the free volume and built water molecule chains in it. Under the Grotthuss mechanism, water molecule chains effectively promote proton transfer. By breaking bonds to provide a channel for proton conduction, the proton conductivity is greatly improved. At the same time, the connection between PBIs is weakened, which makes it easier to cause damage and breakage of the diaphragm when subjected to external force.
[0010] Patent CN118522928A discloses a polybenzimidazole / ionic covalent organic framework composite proton exchange membrane and a preparation method thereof. An ionic covalent organic framework monomer and a catalyst are added to a polybenzimidazole solution and a composite proton exchange membrane is obtained by a solvent volatilization method. The imidazole ring on the polybenzimidazole and the sulfonic acid group of the ionic covalent organic framework are combined through acid-base interaction, which is beneficial to improve the mechanical strength of the composite membrane. However, the bonding force between the two is poor in acid resistance. In a strong acidic environment, the charge distribution of these groups may change, resulting in a weakening of the interaction between them, thereby affecting the stability of the membrane.
[0011] Patent CN118420965A discloses a method for preparing a polybenzimidazole polymer porous membrane regulated by an organic molecular template, wherein an organic small molecule monomer is used as a pore-forming agent, added to a polybenzimidazole solution to form a casting solution, cast on a substrate and dried to obtain a composite membrane, and then acid etching is performed to promote water absorption of the polymer membrane and reduce the impedance of the membrane. The composite membrane obtained by pore formation and acid etching has a high proton conductivity, but this method will also have a certain impact on the mechanical strength of the composite membrane. Summary of the invention
[0012] In order to solve technical problems such as poor bonding between the composite layer and the base layer, and poor overall mechanical properties and alkali resistance of the composite diaphragm, the present invention proposes a porous polybenzimidazole reinforced polyphenylene sulfide composite diaphragm for alkaline water electrolysis hydrogen production and a preparation method thereof. The present invention uses polyphenylene sulfide as a substrate and obtains a porous polybenzimidazole reinforced polyphenylene sulfide composite diaphragm for alkaline water electrolysis hydrogen production having high hydrophilicity, high gas barrier properties, low ohmic resistance and good mechanical properties by compositely adding a porous polybenzimidazole composite material with a reinforcing agent.
[0013] To achieve the above object, the present invention provides the following technical solutions:
[0014] One of the technical solutions of the present invention:
[0015] A method for preparing a porous polybenzimidazole reinforced polyphenylene sulfide composite diaphragm comprises the following steps:
[0016] An organic polymer material based on a polybenzimidazole skeleton is dissolved in an organic solvent, and then a pore-forming agent and a plasticizer are added, stirred, dissolved and mixed evenly to obtain a casting liquid, and the casting liquid is evenly coated on a polyphenylene sulfide diaphragm to obtain a composite diaphragm, and the composite diaphragm is vacuum-dried and then soaked in water, taken out and soaked in an alkaline solution to obtain the porous polybenzimidazole-reinforced polyphenylene sulfide composite diaphragm.
[0017] Furthermore, the organic polymer material based on the polybenzimidazole skeleton is 2,2'-(1,4-naphthalene)-5,5'-dibenzimidazole (NPBI), the pore-forming agent is polyvinyl pyrrolidone (PVP), and the plasticizer is polyethylene glycol (PEG).
[0018] Furthermore, the NPBI is prepared according to the following method: methanesulfonic acid and P2O5 are dissolved in dimethyl sulfoxide, and then 3,3-diaminobenzidine and 1,4-naphthalene dicarboxylic acid are added, and NPBI is synthesized after being fully stirred at 140°C for 12 hours.
[0019] Furthermore, the organic solvent is dimethyl sulfoxide solution (DMSO) or N,N-dimethylacetamide solution (DMA).
[0020] Furthermore, in the casting solution, the concentration of the organic polymer material based on the polybenzimidazole skeleton is 8wt%-15wt%, the concentration of the pore former is 1wt%-1.5wt%, and the concentration of the plasticizer is 2wt%-8wt%.
[0021] Furthermore, the polyphenylene sulfide separator is obtained by placing a polyphenylene sulfide (PPS) support substrate into deionized water and ethanol for thorough cleaning, and then placing it in a vacuum oven for drying.
[0022] Furthermore, the thickness of the polyphenylene sulfide separator is 100 μm-300 μm, and the thickness of the composite separator is 150 μm-500 μm.
[0023] Furthermore, the vacuum drying temperature is not less than 80° C. and the time is not less than 12 hours, in order to evaporate the excess organic solvent.
[0024] Furthermore, the alkali solution is a 3M to 6M KOH solution, and the soaking time in the alkali solution is not less than 7 days.
[0025] Furthermore, the composite membrane is vacuum dried and then soaked in water for 12 hours to 48 hours in order to displace the pore-forming agent.
[0026] The second technical solution of the present invention:
[0027] A porous polybenzimidazole reinforced polyphenylene sulfide composite diaphragm is prepared according to the preparation method.
[0028] The third technical solution of the present invention:
[0029] The porous polybenzimidazole reinforced polyphenylene sulfide composite diaphragm is used in the production of hydrogen by alkaline water electrolysis.
[0030] Compared with the prior art, the present invention has the following advantages and technical effects:
[0031] The porous polybenzimidazole reinforced polyphenylene sulfide composite diaphragm prepared by the present invention has good mechanical properties and bonding strength, good hydrophilicity and low surface resistance. Specifically:
[0032] (1) Good mechanical properties and bonding strength
[0033] The polymer material used in the present invention is a polymer (NPBI) formed by connecting benzimidazole units through naphthalene groups. The presence of naphthyl groups makes the chemical properties of the material more stable, but also makes the rigidity of the material stronger, resulting in its ductility becoming worse after film formation, and it is easy to break brittle under external force. In order to overcome this shortcoming, the present invention introduces polyethylene glycol (PEG) in the film forming process, which is a long-chain polymer compound. This long-chain structure gives polyethylene glycol good flexibility and is not easy to break brittle. Therefore, the present invention adopts a filling method to fully mix naphthyl benzimidazole polymer and PEG to form a casting liquid, and the casting liquid is filled into the pores of the PPS substrate at the same time. The good flexibility of PEG can make the casting liquid better wrap the PPS fiber, thereby improving the bonding force with the PPS substrate, forming a composite diaphragm with strong flexibility and mechanical strength, which is not easy to break and fall off.
[0034] (2) Good hydrophilicity and low surface resistance
[0035] The PEG used in the present invention is a polyhydroxy structure, which improves the hydrophilicity of the composite membrane, and the addition of the pore-forming agent PVP increases the micro-nano pores that are conducive to ion conduction, further improves the hydrophilicity of the composite membrane, and reduces its surface resistance.
[0036] The present invention optimizes the addition ratio of the plasticizer PEG and the pore-forming agent PVP, so that the composite diaphragm has both good hydrophilicity and low surface resistance as well as good toughness and mechanical strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0038] Figure 1 This is a water contact angle effect diagram of the porous polybenzimidazole reinforced polyphenylene sulfide composite membrane prepared in Example 1 of the present invention;
[0039] Figure 2 This is a water contact angle effect diagram of the polyphenylene sulfide composite diaphragm prepared in Example 2 of the present invention;
[0040] Figure 3 This is a water contact angle effect diagram of the polyphenylene sulfide composite diaphragm prepared in Comparative Example 1 of the present invention;
[0041] Figure 4 The scanning electron microscope images of the polyphenylene sulfide composite diaphragm prepared in Example 1 of the present invention, wherein (a) and (b) are scanning electron microscope images of the cross section of the polyphenylene sulfide composite diaphragm at different magnifications, and (c) is a scanning electron microscope image of the surface of the polyphenylene sulfide composite diaphragm;
[0042] Figure 5 The scanning electron microscope images of the polyphenylene sulfide composite diaphragm prepared in Example 2 of the present invention, wherein (a) and (b) are scanning electron microscope images of the cross section of the polyphenylene sulfide composite diaphragm at different magnifications, and (c) is a scanning electron microscope image of the surface of the polyphenylene sulfide composite diaphragm;
[0043] Figure 6 The present invention is a scanning electron microscope image of the polyphenylene sulfide composite membrane prepared in Comparative Example 1, wherein (a) and (b) are scanning electron microscope images of the cross section of the polyphenylene sulfide composite membrane at different magnifications, and (c) is a scanning electron microscope image of the surface of the polyphenylene sulfide composite membrane;
[0044] Figure 7 The infrared spectra of the polyphenylene sulfide composite membranes prepared in Example 1, Example 2 and Comparative Example 1 of the present invention are shown;
[0045] Figure 8 This is a graph showing the tensile strength and elongation results of the polyphenylene sulfide composite diaphragms prepared in Example 1, Example 2, Example 3, Example 4, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0046] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0047] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0048] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0049] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0050] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0051] The embodiment of the present invention provides a method for preparing a porous polybenzimidazole reinforced polyphenylene sulfide composite diaphragm, comprising the following steps:
[0052] An organic polymer material based on a polybenzimidazole skeleton is dissolved in an organic solvent, and then a pore-forming agent and a plasticizer are added, stirred, dissolved and mixed evenly to obtain a casting liquid, and the casting liquid is evenly coated on a polyphenylene sulfide diaphragm to obtain a composite diaphragm, and the composite diaphragm is vacuum-dried and then soaked in water, taken out and soaked in an alkaline solution to obtain the porous polybenzimidazole-reinforced polyphenylene sulfide composite diaphragm.
[0053] In a preferred embodiment of the present invention, the organic polymer material based on the polybenzimidazole skeleton is 2,2'-(1,4-naphthalene)-5,5'-dibenzimidazole (NPBI), the pore-forming agent is polyvinyl pyrrolidone (PVP), and the plasticizer is polyethylene glycol (PEG).
[0054] NPBI used in the embodiment of the present invention is a polymer formed by connecting benzimidazole units through naphthalene groups. The presence of naphthalene makes the chemical properties of the material more stable, but it also makes the rigidity of the material stronger, resulting in its ductility becoming worse after film formation, and it is easy to break brittle under the action of external force. In order to overcome this shortcoming, the present invention introduces polyethylene glycol (PEG) in the film forming process. It is a long-chain polymer compound. This long-chain structure gives polyethylene glycol good flexibility and is not easy to break brittle. Therefore, the embodiment of the present invention adopts a filling method to completely mix naphthylbenzimidazole polymer and PEG to form a casting liquid, and at the same time, the casting liquid is filled into the pores of the PPS substrate. The good flexibility of PEG can make the casting liquid better wrap around the PPS fiber, thereby improving the bonding force with the PPS substrate, forming a composite diaphragm with strong flexibility and mechanical strength, which is not easy to break and fall off. In addition, PEG is a polyhydroxy structure, which improves the hydrophilicity of the composite membrane. The addition of the pore-forming agent PVP increases the micro-nano pores that are conducive to ion conduction, further improving the hydrophilicity of the composite membrane and reducing its surface resistance.
[0055] More specifically, the NPBI is prepared according to the following method:
[0056] (1) 30 g of methanesulfonic acid (analytical grade) and 3 g of P2O5 (analytical grade) were added to a 100 mL flask equipped with a mechanical stirrer, and the mixture was stirred at 55° C. until P2O5 was completely dissolved to prepare Eaton's reagent;
[0057] (2) In a mechanically stirred 250 mL three-necked flask, 25 g of Eaton's reagent, 2.15 g of 3,3-diaminobenzidine (analytical grade), and 2.16 g of 1,4-naphthalene dicarboxylic acid (analytical grade) were added, and the mixture was stirred at 140° C. under a nitrogen atmosphere for 12 hours to synthesize NPBI.
[0058] In a preferred embodiment of the present invention, the organic solvent is dimethyl sulfoxide solution (DMSO) or N,N-dimethylacetamide solution (DMA).
[0059] In a preferred embodiment of the present invention, in the casting solution, the concentration of the organic polymer material based on the polybenzimidazole skeleton is 8wt%-15wt%, the concentration of the pore former is 1wt%-1.5wt%, and the concentration of the plasticizer is 2wt%-8wt%.
[0060] In a preferred embodiment of the present invention, the polyphenylene sulfide membrane is obtained by fully washing a polyphenylene sulfide (PPS) support substrate in deionized water and ethanol, and then drying it in a vacuum oven.
[0061] In a preferred embodiment of the present invention, the thickness of the polyphenylene sulfide membrane is 100 μm-300 μm, preferably 250 μm, and the thickness of the composite membrane is 150 μm-500 μm, preferably 300 μm.
[0062] In a preferred embodiment of the present invention, the vacuum drying temperature is not less than 80° C. and the time is not less than 12 hours, in order to evaporate the excess organic solvent.
[0063] In a preferred embodiment of the present invention, the alkali solution is a 3M-6M (preferably 6M) KOH solution, and the soaking time in the alkali solution is 7 days.
[0064] In a preferred embodiment of the present invention, the composite membrane is vacuum dried and then soaked in water for 12 hours to 48 hours (preferably 12 hours) in order to displace the pore-forming agent.
[0065] In a preferred embodiment of the present invention, there is no special restriction on the amount of alkali solution and water used in the soaking process, as long as the amount of alkali solution and water used does not exceed the composite diaphragm.
[0066] The embodiment of the present invention further provides a porous polybenzimidazole reinforced polyphenylene sulfide composite diaphragm, which is prepared according to the preparation method.
[0067] The organic solvent, PVP, PEG and polyphenylene sulfide (PPS) support substrate (thickness of 250 μm) used in the embodiments of the present invention are all commercially available.
[0068] The technical solution of the present invention is further illustrated by the following embodiments.
[0069] Example 1
[0070] (1) NPBI was added to 10 ml of dimethyl sulfoxide (DMSO). After NPBI was completely dissolved, PVP was added as a pore-forming agent, and then PEG was added as a plasticizer. The mixture was mechanically stirred for 12 h to completely dissolve and mix the NPBI to obtain a casting solution. The concentration of NPBI in the casting solution was 8 wt %, the concentration of PVP was 1 wt %, and the concentration of PEG was 8 wt %;
[0071] (2) The polyphenylene sulfide (PPS) support substrate is placed in deionized water and ethanol for thorough cleaning, and then placed in a vacuum oven for drying to obtain a PPS diaphragm, and the casting solution obtained in step (1) is evenly coated on the treated PPS diaphragm by a doctor blade coating method, so that the average formed thickness of the composite diaphragm is 300 μm;
[0072] (3) placing the composite membrane prepared in step (2) in a vacuum oven, drying at 100° C. for 12 h, taking out and cooling, and then soaking the composite membrane in water for 12 h to displace the PVP to achieve the purpose of pore formation;
[0073] (4) Soaking the composite diaphragm prepared in step (3) in 6M alkali solution for 7 days for alkali doping, and then taking it out to obtain a porous polybenzimidazole reinforced polyphenylene sulfide composite diaphragm.
[0074] Example 2
[0075] (1) NPBI was added to 10 ml of dimethyl sulfoxide (DMSO). After NPBI was completely dissolved, PVP was added as a pore-forming agent, and then PEG was added as a plasticizer. The mixture was mechanically stirred for 12 h to completely dissolve and mix the NPBI to obtain a casting solution. The concentration of NPBI in the casting solution was 8 wt %, the concentration of PVP was 1 wt %, and the concentration of PEG was 3 wt %;
[0076] (2) The polyphenylene sulfide (PPS) support substrate is placed in deionized water and ethanol for thorough cleaning, and then placed in a vacuum oven for drying to obtain a PPS diaphragm, and the casting solution obtained in step (1) is evenly coated on the treated PPS diaphragm by a doctor blade coating method, so that the average formed thickness of the composite diaphragm is 300 μm;
[0077] (3) placing the composite membrane prepared in step (2) in a vacuum oven, drying at 100° C. for 12 h, taking out and cooling, and then soaking the composite membrane in water for 12 h to displace the PVP to achieve the purpose of pore formation;
[0078] (4) Soaking the composite diaphragm prepared in step (3) in 6M alkali solution for 7 days for alkali doping, and then taking it out to obtain a porous polybenzimidazole reinforced polyphenylene sulfide composite diaphragm.
[0079] Example 3
[0080] 1) NPBI was added to 10 ml of dimethyl sulfoxide (DMSO). After NPBI was completely dissolved, PVP was added as a pore-forming agent, and then PEG was added as a plasticizer. The mixture was mechanically stirred for 12 hours to completely dissolve and mix the NPBI to obtain a casting solution. The concentration of NPBI in the casting solution was 8 wt %, the concentration of PVP was 1.5 wt %, and the concentration of PEG was 8 wt %;
[0081] (2) The polyphenylene sulfide (PPS) support substrate is placed in deionized water and ethanol for thorough cleaning, and then placed in a vacuum oven for drying to obtain a PPS diaphragm, and the casting solution obtained in step (1) is evenly coated on the treated PPS diaphragm by a doctor blade coating method, so that the average formed thickness of the composite diaphragm is 300 μm;
[0082] (3) placing the composite membrane prepared in step (2) in a vacuum oven, drying at 100° C. for 12 h, taking out and cooling, and then soaking the composite membrane in water for 12 h to displace the PVP to achieve the purpose of pore formation;
[0083] (4) Soaking the composite diaphragm prepared in step (3) in 6M alkali solution for 7 days for alkali doping, and then taking it out to obtain a porous polybenzimidazole reinforced polyphenylene sulfide composite diaphragm.
[0084] Example 4
[0085] (1) NPBI was added to 10 ml of dimethyl sulfoxide (DMSO). After NPBI was completely dissolved, PVP was added as a pore-forming agent, and then PEG was added as a plasticizer. The mixture was mechanically stirred for 12 h to completely dissolve and mix the NPBI to obtain a casting solution. The concentration of NPBI in the casting solution was 15 wt %, the concentration of PVP was 1 wt %, and the concentration of PEG was 8 wt %;
[0086] (2) The polyphenylene sulfide (PPS) support substrate is placed in deionized water and ethanol for thorough cleaning, and then placed in a vacuum oven for drying to obtain a PPS diaphragm, and the casting solution obtained in step (1) is evenly coated on the treated PPS diaphragm by a doctor blade coating method, so that the average formed thickness of the composite diaphragm is 300 μm;
[0087] (3) placing the composite membrane prepared in step (2) in a vacuum oven, drying at 100° C. for 12 h, taking out and cooling, and then soaking the composite membrane in water for 12 h to displace the PVP to achieve the purpose of pore formation;
[0088] (4) Soaking the composite diaphragm prepared in step (3) in 6M alkali solution for 7 days for alkali doping, and then taking it out to obtain a porous polybenzimidazole reinforced polyphenylene sulfide composite diaphragm.
[0089] Comparative Example 1
[0090] (1) NPBI was added to 10 ml of dimethyl sulfoxide (DMSO) and mechanically stirred for 12 h to completely dissolve and mix the NPBI to obtain a casting solution, wherein the concentration of NPBI in the casting solution was 8 wt %;
[0091] (2) The polyphenylene sulfide (PPS) support substrate is placed in deionized water and ethanol for thorough cleaning, and then placed in a vacuum oven for drying to obtain a PPS diaphragm, and the casting solution obtained in step (1) is evenly coated on the treated PPS diaphragm by a doctor blade coating method, so that the average formed thickness of the composite diaphragm is 300 μm;
[0092] (3) placing the composite membrane prepared in step (2) in a vacuum oven, drying at 100° C. for 12 h, taking out and cooling, and then soaking the composite membrane in water for 12 h to displace the PVP to achieve the purpose of pore formation;
[0093] (4) Soaking the composite diaphragm prepared in step (3) in 6M alkali solution for 7 days for alkali doping, and then taking it out to obtain a polyphenylene sulfide composite diaphragm.
[0094] Comparative Example 2
[0095] (1) NPBI was added to 10 ml of dimethyl sulfoxide (DMSO). After NPBI was completely dissolved, PEG was added as a plasticizer and mechanically stirred for 12 h to completely dissolve and mix the NPBI to obtain a casting solution. The concentration of NPBI in the casting solution was 8 wt %, the concentration of PEG was 8 wt %, and the concentration of PVP was 3 wt %;
[0096] (2) The polyphenylene sulfide (PPS) support substrate is placed in deionized water and ethanol for thorough cleaning, and then placed in a vacuum oven for drying to obtain a PPS diaphragm, and the casting solution obtained in step (1) is evenly coated on the treated PPS diaphragm by a doctor blade coating method, so that the average formed thickness of the composite diaphragm is 1000 μm;
[0097] (3) placing the composite membrane prepared in step (2) in a vacuum oven, drying at 100° C. for 12 h, taking out and cooling, and then soaking the composite membrane in water for 12 h to displace the PVP to achieve the purpose of pore formation;
[0098] (4) Soaking the composite diaphragm prepared in step (3) in 6M alkali solution for 7 days for alkali doping, and then taking it out to obtain a polyphenylene sulfide composite diaphragm.
[0099] Comparative Example 3
[0100] (1) Synthesis of mPBI (meta-aromatic polybenzimidazole): 30 g of methanesulfonic acid (analytical grade) and 3 g of P2O5 (analytical grade) were added to a 100 mL flask equipped with a mechanical stirrer, and the mixture was stirred at 55°C until P2O5 was completely dissolved to prepare Eaton's reagent; 25 g of Eaton's reagent, 2.15 g of 3,3-diaminobenzidine (analytical grade) and 1.65 g of isophthalic acid (analytical grade) were added to a 250 mL three-necked flask with mechanical stirring, and the mixture was stirred at 140°C under a nitrogen atmosphere for 12 hours to synthesize mPBI;
[0101] (2) adding the mPBI synthesized in step (1) into 10 ml of dimethyl sulfoxide (DMSO), adding PVP as a pore-forming agent after the mPBI is completely dissolved, and then adding PEG as a plasticizer, and mechanically stirring for 12 hours to completely dissolve and mix the mPBI to obtain a casting solution, wherein the concentration of mPBI in the casting solution is 8 wt %, the concentration of PVP is 1 wt %, and the concentration of PEG is 8 wt %;
[0102] (3) The polyphenylene sulfide (PPS) support substrate is placed in deionized water and ethanol for thorough cleaning, and then placed in a vacuum oven for drying to obtain a PPS diaphragm, and the casting solution obtained in step (1) is evenly coated on the treated PPS diaphragm by a doctor blade method, so that the average formed thickness of the composite diaphragm is 300 μm;
[0103] (4) placing the composite membrane prepared in step (3) in a vacuum oven, drying at 100° C. for 12 h, taking out and cooling, and then soaking the composite membrane in water for 12 h to displace the PVP to achieve the purpose of pore formation;
[0104] (5) Soaking the composite diaphragm prepared in step (4) in 6M alkali solution for 7 days for alkali doping, and then taking it out to obtain a polyphenylene sulfide composite diaphragm.
[0105] Performance Testing
[0106] (1) The polyphenylene sulfide composite membranes prepared in Examples 1-4 and Comparative Examples 1-3 of the present invention were tested for water contact angle and scanning electron microscopy:
[0107] The water contact angle of the polyphenylene sulfide composite membrane prepared in Example 1 of the present invention is 43°, the water contact angle of the polyphenylene sulfide composite membrane in Example 2 is 63°, the water contact angle of the polyphenylene sulfide composite membrane in Example 3 is 39°, the water contact angle of the polyphenylene sulfide composite membrane in Example 4 is 60°, the water contact angle of the polyphenylene sulfide composite membrane in Comparative Example 1 is 86°, the water contact angle of the polyphenylene sulfide composite membrane in Comparative Example 2 is 50°, and the water contact angle of the polyphenylene sulfide composite membrane in Comparative Example 3 is 88°. Among them, the water contact angle effect diagram of the porous polybenzimidazole reinforced polyphenylene sulfide composite membrane prepared in Example 1 of the present invention is shown in Figure 1 The water contact angle effect diagram of the polyphenylene sulfide composite diaphragm prepared in Example 2 of the present invention is shown in Figure 2 The water contact angle effect diagram of the polyphenylene sulfide composite diaphragm prepared in Comparative Example 1 of the present invention is shown in Figure 3 According to the water contact angle measurement results, it can be concluded that with the addition of the pore-forming agent PVP, the pores inside the diaphragm increase, the water absorption rate increases, and the water contact angle of the composite diaphragm decreases, thereby reducing the surface resistance of the polyphenylene sulfide composite diaphragm.
[0108] The scanning electron microscope images of the polyphenylene sulfide composite membranes prepared in Examples 1 and 2 of the present invention and Comparative Example 1 are shown in FIG. Figure 4 , Figure 5 , Figure 6 , wherein (a) and (b) are scanning electron microscope images of the cross section of the polyphenylene sulfide composite membrane at different magnifications, and (c) is a scanning electron microscope image of the surface of the polyphenylene sulfide composite membrane. It can be seen that, compared with the comparative example, after adding the PVP pore-forming agent, certain holes are formed in the polybenzimidazole composite membrane in Example 1 of the present invention, and the diameter of the holes is about 50 nm. More open pores are conducive to the entry of KOH electrolyte into the membrane, thereby improving the conductivity of the membrane. In addition, the surface of the polybenzimidazole composite membrane in Example 1 is very smooth and dense, which can effectively prevent the mixing of hydrogen and oxygen.
[0109] (2) The infrared spectra of the polyphenylene sulfide composite membranes of Example 1, Example 2 and Comparative Example 1 of the present invention are shown in FIG. Figure 7 It can be seen that Example 1 and Comparative Example 1 have -1 The peak of PEG COC is newly added, indicating that PEG has been integrated into the polybenzimidazole membrane. The other peaks of Example 1 show the same characteristic absorption peaks as those of Comparative Example 2, which means that the PVP in Example 1 is completely removed in the leaching step, and it also shows that the introduction of PVP will not affect the chemical structure of the polybenzimidazole composite membrane.
[0110] (3) The surface resistance of the polyphenylene sulfide composite membranes prepared in Examples 1-4 and Comparative Examples 1-3 was tested using Princeton PARSTAT 3000-DX, the pure gas permeability of the composite membranes was evaluated using a constant current volume permeameter, and the tensile strength and elongation at break were measured using a universal tensile machine. The results are shown in Tables 1 and Figure 8 .
[0111] Table 1 Performance test results of polyphenylene sulfide composite diaphragm of Examples 1-4 and Comparative Examples 1-3
[0112]
[0113] Combining Table 1 and Figure 8 It can be seen that: with the increase of plasticizer PEG, the surface resistance of the diaphragm decreases and the elongation at break increases, indicating that the plasticizer PEG can indeed enhance the elongation at break of the diaphragm; the mechanical strength of the polyphenylene sulfide composite diaphragm gradually decreases with the increase of PVP, because the increase of PVP content leads to more pores inside the polyphenylene sulfide composite diaphragm, thereby reducing the mechanical properties and air tightness of the polyphenylene sulfide composite diaphragm. At the same time, the higher the PVP content, the easier it is for the composite membrane to form continuous OH - The smaller the conduction resistance of the transmission channel, the smaller the surface resistance. The tensile strength of the polyphenylene sulfide composite membrane increases with the increase of the NPBI content, and the elongation at break decreases. This is mainly because NPBI has good mechanical properties and rigidity. The increase in its content can enhance the mechanical strength of the composite membrane, resulting in poor ductility after film formation and a decrease in the elongation at break. It can be seen from Example 1 and Comparative Example 3 that different types of PBI also have different mechanical strengths. The mechanical strength of the polyphenylene sulfide composite membrane of Comparative Example 3 is reduced by 16.8% compared to the above.
[0114] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a porous polybenzimidazole reinforced polyphenylene sulfide composite diaphragm, characterized in that: The following steps are involved: An organic polymer material based on a polybenzimidazole skeleton is dissolved in an organic solvent, and then a pore-forming agent and a plasticizer are added, stirred, dissolved and mixed evenly to obtain a casting liquid, and the casting liquid is evenly coated on a polyphenylene sulfide diaphragm to obtain a composite diaphragm, and the composite diaphragm is vacuum-dried and then soaked in water, taken out and soaked in an alkaline solution to obtain the porous polybenzimidazole-reinforced polyphenylene sulfide composite diaphragm.
2. The method for preparing the porous polybenzimidazole reinforced polyphenylene sulfide composite diaphragm according to claim 1, characterized in that: The organic polymer material based on the polybenzimidazole skeleton is 2,2'-(1,4-naphthalene)-5,5'-dibenzimidazole, the pore-forming agent is polyvinyl pyrrolidone, and the plasticizer is polyethylene glycol.
3. The method for preparing the porous polybenzimidazole reinforced polyphenylene sulfide composite diaphragm according to claim 1, characterized in that: In the casting solution, the concentration of the organic polymer material based on the polybenzimidazole skeleton is 8wt%-15wt%, the concentration of the pore former is 1wt%-1.5wt%, and the concentration of the plasticizer is 2wt%-8wt%.
4. The method for preparing the porous polybenzimidazole reinforced polyphenylene sulfide composite diaphragm according to claim 1, characterized in that: The thickness of the polyphenylene sulfide diaphragm is 100 μm-300 μm, and the thickness of the composite diaphragm is 150 μm-500 μm.
5. The method for preparing the porous polybenzimidazole reinforced polyphenylene sulfide composite diaphragm according to claim 1, characterized in that: The vacuum drying temperature is not less than 80° C. and the time is not less than 12 hours.
6. The method for preparing the porous polybenzimidazole reinforced polyphenylene sulfide composite diaphragm according to claim 1, characterized in that: The alkali solution is a 3M-6M KOH solution, and the soaking time in the alkali solution is not less than 7 days.
7. The method for preparing the porous polybenzimidazole reinforced polyphenylene sulfide composite diaphragm according to claim 1, characterized in that: The composite diaphragm is vacuum dried and then soaked in water for 12h-48h.
8. A porous polybenzimidazole reinforced polyphenylene sulfide composite diaphragm, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 7.
9. Use of the porous polybenzimidazole reinforced polyphenylene sulfide composite membrane as claimed in claim 8 in hydrogen production by alkaline water electrolysis.